Physical Modeling of Charge Trapping Effects in GaN/Si Devices and Incorporation in the ASM-HEMT Model - Mamta Pradhan; Mohammed Alomari; Matthias Moser; Dirk Fahle; Herwig Hahn; Michael Heuken; Joachim N. Burghartz (IEEE Journal of the Electron Devices Society, 2021)
In this work, the dynamic behavior of gallium nitride on silicon high electron mobility transistors (GaN/Si HEMT) with carbon doped buffer is modeled using a finite state machine embedded into the core Advanced SPICE Model for High Electron Mobility Transistor (ASM-HEMT). The model is based on the physics of trapping and detrapping of electrons in carbon at nitrogen-site acceptor trap (denoted here as $\text{C}_{N}$ ) and does not require an equivalent Resistance-Capacitance circuit. The model is validated against three off-state stress drain voltages of 50 V, 100 V, and 150 V using only $\text{C}_{N}$ as trap species.